Effects of salt stress on proline content, expression of delta-1-pyrroline-5-carboxylate synthetase, and activities of catalase and ascorbate peroxidase in transgenic tobacco plants - Razavizadeh, Roya; Ehsanpour, Ali (Biological Letters, 2010)
In arid and semiarid regions, soil salinity limits crop production. Proline accumulation in transgenic plants results in increased stress tolerance, but the underlying mechanism was unclear. To elucidate it, effects of salt stress on the expression pattern of Δ1-pyrroline-5-carboxylate synthetase (P5CS), proline content, catalase (CAT), and ascorbate peroxidase (APX) activities were analyzed in transgenic tobacco (Nicotiana tabacum cv. Wisconsin). Transgenic tobacco plants containing CaMV 35S promoter and the P5CS gene from moth bean (Vigna aconitifolia), linked to the NPTII gene, were cultured in vitro with or without 300 mM NaCl. The expression pattern of P5CS was evaluated using semiquantitative RT-PCR (reverse transcription-polymerase chain reaction). Time-course experiments showed an increase in proline content after 4 h of the treatment. The level of P5CS transcripts was increased significantly in leaves and roots of transgenic plants after 24 and 48 h of treatment. This rise in transcripts was concomitant with the highest increase in proline content. In addition, CAT and APX activities increased under salt stress, and their highest activities were observed after 24 and 48 h of NaCl treatment. These results suggest that P5CS is an inducible gene regulating the activities of CAT and APX and the accumulation of proline in plants subjected to salt stress.